2017
DOI: 10.1155/2017/8529542
|View full text |Cite
|
Sign up to set email alerts
|

Humanβ-Defensin 3 Reduces TNF-α-Induced Inflammation and Monocyte Adhesion in Human Umbilical Vein Endothelial Cells

Abstract: The aim of this study was to investigate the role of human β-defensin 3 (hBD3) in the initiation stage of atherosclerosis with human umbilical vein endothelial cells (HUVECs) triggered by tumor necrosis factor- (TNF-) α. The effects of hBD3 on TNF-α-induced endothelial injury and inflammatory response were evaluated. Our data revealed that first, hBD3 reduced the production of interleukin-6 (IL-6), IL-8, monocyte chemoattractant protein-1 (MCP-1), and macrophage migration inhibitory factor (MIF) in HUVECs in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 50 publications
1
19
0
Order By: Relevance
“…It has been reported that the hβD3 expression level in gingival tissues and crevicular fluid is decreased in patients with periodontitis in comparison to healthy controls (29). It has been found that hβD3 reduced the level of ICAM-1 protein and inhibits the phosphorylation of NF-κB induced by TNF-α, which is consistent with a finding obtained in HUVECs (26). Although it was not statistically significant, S1PC at 10 µM exhibited near the maximal inhibition induced by S1PC at 100 µM on the elevated ICAM-1 protein by TNF-α (Fig.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…It has been reported that the hβD3 expression level in gingival tissues and crevicular fluid is decreased in patients with periodontitis in comparison to healthy controls (29). It has been found that hβD3 reduced the level of ICAM-1 protein and inhibits the phosphorylation of NF-κB induced by TNF-α, which is consistent with a finding obtained in HUVECs (26). Although it was not statistically significant, S1PC at 10 µM exhibited near the maximal inhibition induced by S1PC at 100 µM on the elevated ICAM-1 protein by TNF-α (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…It has been previously demonstrated that the anti-microbial peptide hβD3 reduces the level of TNF-α-elicited ICAM-1 protein in human vein endothelial cells (HUVECs) (26). Thus, this study examined whether the peptide inhibits the level of ICAM-1 protein in Ca9-22 cells.…”
Section: Effect Of S1pc and Hβd3 On The Level Of Icam-1 Protein Inducmentioning
confidence: 97%
See 1 more Smart Citation
“…It is also reported that BDs are capable of electrostatically interacting with negatively charged components in microbial cell walls, by increasing the permeability of cell walls and ultimately leading to a host cell death ( 9 ). In addition to their antimicrobial function, BDs also function as inflammatory mediators, with impact on the immune activation of epithelial cells and immunocytes ( 10 , 11 ), production of inflammatory cytokines ( 12 , 13 ), as well as induction of chemotaxis ( 7 , 14 ). For instance, Beta-defensins 2 (BD2) has been shown to chemoattract immature dendritic cells or memory CD4 + T cells through C–C motif chemokine receptor 6 ( 7 ), while beta-defensins 3 (BD3) and BD4 recruit macrophages dependent on cysteine residues ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we observed that AuNPs and hBD3 slightly increased the viability of hPDLCs with the stimulation of E. coli-LPS, which was in agreement with previous reports. 9,22 In addition to the biotoxicity, cellular uptake was another essential component in the cellular response to AuNPs. In this study, 45 nm AuNPs were internalized according to observations of one or two spherical shapes clustered together.…”
mentioning
confidence: 99%